A new integrated approach for dye removal from wastewater by polyoxometalates functionalized membranes - Yao, Lei (2015)
Membrane technique is a promising way for the removal of dyes from wastewater. A unique approach combining both the adsorptive and the catalytic membrane processes was proposed on the basis of a new functionalized membrane. The membrane integrating both the adsorptive and catalytic activities was developed by introducing polyoxometalates (POMs) as an ideal candidate for the membrane functionalization via a novel sol–gel method. A two-step protocol, adsorptive separation and catalytic degradation, was designed for dye removal, realizing an excellent dye rejection with easy and economic membrane regeneration through simply soaking the membrane in a limited volume of dilute oxidant solution. This approach is feasible and versatile owing to the flexible selection of distinct POMs and design of catalytic degradation routes as required. As a result, the current research provides insight into a new methodology of the membrane technique in dye removal applications.